2013
DOI: 10.1002/14651858.cd004469.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for brain abscesses in people with cyanotic congenital heart disease

Abstract: There are no randomized controlled trials about the effectiveness of antibiotic regimens for treating people with cyanotic congenital heart disease who developed a brain abscess. Currently, the antibiotic regimens used are based on previous retrospective studies and clinical experience. There is a need for a well designed multicentre randomized controlled trial to evaluate the effects of different antibiotic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
15
0
4
Order By: Relevance
“…Regarding antibiotic therapy for the past 20 years high dose intravenous penicillin G and chloramphenicol have been used to treat brain abscess in this setting with satisfactory outcomes [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding antibiotic therapy for the past 20 years high dose intravenous penicillin G and chloramphenicol have been used to treat brain abscess in this setting with satisfactory outcomes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, metronidazole is usually combined with third generation cephalosporins or penicillin G for the treatment of the patients with cyanotic heart disease complicated with BA [14]. The third generation cephalosporins are much more expensive than penicillin G there is a need to evaluate their effects [15].…”
Section: Discussionmentioning
confidence: 99%
“…In cyanotic CHD, the presence of an intracardiac right-left shunt let the bacteria escape the filter represented by alveolar macrophages in the lungs. 9 One study demonstrated an impairment of phagocytic and bactericidal function in the leucocytes of infants affected by cyanotic CHD. 9 This kind of CHD often leads to development of complications involving the central nervous system, most often brain abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…9 One study demonstrated an impairment of phagocytic and bactericidal function in the leucocytes of infants affected by cyanotic CHD. 9 This kind of CHD often leads to development of complications involving the central nervous system, most often brain abscesses. 10 With regard to noncyanotic cardiopathies, in the literature, a few cases of cerebral abscess associated with an interventricular communication or an interatrial communication have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary circulation represents a potential filtering apparatus for systemic bacterial pathogens. In patients with right-to-left shunts, absence of pulmonary phagocytic clearance of pathogens can occur and the ischemic injury from hypoxaemia and polycythaemia, produce low perfusion areas (microinfarcts) in the brain which may act as a nidus for infection [18]. In the development of brain abscess, inoculation of an organism is required into the brain parenchyma in an area of devitalized brain tissue or in a region with poor microcirculation and the seeded microorganisms can sustain growth and multiply to form abscess.…”
Section: Etiopathogenesismentioning
confidence: 99%